1999
DOI: 10.1152/jappl.1999.87.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of brief daily tendon vibration on rat soleus muscle in non-weight-bearing situation

Abstract: The purpose of this study was to investigate whether tendon vibration could prevent soleus muscle atrophy during hindlimb unloading (HU). Mechanical vibrations with a constant low amplitude (0.3 mm) were applied (192 s/day) with constant frequency (120 Hz) to the Achilles tendon of the unloaded muscle during the 14-day HU period. Significant reductions in muscle mass (-41%), fiber size, maximal twitch (-54%), and tetanic tensions (-73%) as well as changes in fiber type and electrophoretic profiles and twitch-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…Together, these reports suggest that VAT has an effect similar to aerobic exercise through activation of the p38MAPK pathway. Falempin et al suggested that tendon vibration (120 Hz) applied to rat soleus muscle can be used as a strategy to counteract the atrophic process observed after hindlimb unloading 32) . In addition, Skill reported that vibroacoustic music (30-120 Hz) reduces muscle tone and spasms 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Together, these reports suggest that VAT has an effect similar to aerobic exercise through activation of the p38MAPK pathway. Falempin et al suggested that tendon vibration (120 Hz) applied to rat soleus muscle can be used as a strategy to counteract the atrophic process observed after hindlimb unloading 32) . In addition, Skill reported that vibroacoustic music (30-120 Hz) reduces muscle tone and spasms 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, during HU, the soleus muscle spindles were probably little, or not at all, stimulated and the afferent activity of Ia and II fibers originating from these stretch receptors was reduced. Indeed, the reactivation of Ia fibers by tendinous vibrations has been reported as an effective countermeasure preventing muscle atrophy developed during HU, thus indicating that proprioceptive information was greatly disrupted in this condition (Falempin and In-Albon, 1999).…”
Section: Immediately After Humentioning
confidence: 97%
“…Moreover, during HU, the soleus was often in a shortened position as after tenotomy and immobilization in a plantar flexion position (Riley et al, 1990), the natural physiological stimulus of muscle spindles, the muscular stretch, being thus removed and muscle spindle discharges decreased. However, the intermittent application of brief daily tendon vibration for 14 days in HU condition (soleus stretched during application of vibrations) prevented 75% of the soleus muscular atrophy (Falempin and In-Albon, 1999). This indicated that during HU, afferent messages from muscle spindles are decreased because of plantar flexion and contribute to the development of the soleus atrophy.…”
mentioning
confidence: 96%
“…The animals were anesthetized with pentobarbital sodium (40 mg/kg ip), and anesthesia was prolonged with further injections of 20 mg/kg, when necessary. The dissection protocol has been described in previous papers originating from our laboratory (12,19). Briefly, under deep anesthesia, assessed by the absence of blink reflexes, all the muscles of the right thigh and lower limb were denervated, except the soleus muscle.…”
Section: Methodsmentioning
confidence: 99%